2013
DOI: 10.1007/s11882-012-0335-7
|View full text |Cite
|
Sign up to set email alerts
|

New Directions in Immunotherapy

Abstract: Allergen immunotherapy (AIT) is effective in reducing the clinical symptoms associated with allergic rhinitis, asthma and venom-induced anaphylaxis. Subcutaneous (SCIT) and sublingual immunotherapy (SLIT) with unmodified allergen extracts are the most widely prescribed AIT regimens. The efficacy of these 2 routes appears comparable, but the safety profile with SLIT is more favorable allowing for home administration and requiring less patient time. However, both require that the treatment is taken regularly ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
38
0
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 181 publications
0
38
0
3
Order By: Relevance
“…Other forms of immunotherapy are sought for more convenient and safer options to treat the large number of allergic individuals who could benefit greatly from informahealthcare.com 10 AIT. The rationale of reducing the allergenicity of allergen extracts to increase safety while maintaining and improving immunogenicity has led to exploration of different routes for delivery and modification of allergens with promising advances over recent years [19,20]. Additionally, adjuvants, adjunct therapies and allergen-independent forms of 'immunotherapy', such as Toll-like receptor (TLR) agonists as monotherapy have been explored as potential new therapies.…”
mentioning
confidence: 99%
“…Other forms of immunotherapy are sought for more convenient and safer options to treat the large number of allergic individuals who could benefit greatly from informahealthcare.com 10 AIT. The rationale of reducing the allergenicity of allergen extracts to increase safety while maintaining and improving immunogenicity has led to exploration of different routes for delivery and modification of allergens with promising advances over recent years [19,20]. Additionally, adjuvants, adjunct therapies and allergen-independent forms of 'immunotherapy', such as Toll-like receptor (TLR) agonists as monotherapy have been explored as potential new therapies.…”
mentioning
confidence: 99%
“…OIT may offer a promising approach to induce specific oral tolerance to selected food allergens, though yet restricted to a small group of molecules, and can represent a potential strategy for long-term curative treatment of food allergy, 125 though many controversial problems about protocol and allergen dose yet exist, even for other AIT protocols. [143][144][145][146][147][148][149][150] The application of BAT in oral immunotherapy should consider also the role of secretory IgAs and their receptor on granulocytes. [151][152][153] Past reports have shown that secretory IgAs induce degranulation in IL-3 primed basophils.…”
Section: Immunotherapy With Allergens and Bat: Oral Immunotherapy (Oimentioning
confidence: 99%
“…Subcutanous (SCIT) or sublingual (SLIT) immunotherapy are the most widely accepted routes of immunotherapy administration. The efficacy of oral immunotherapy (OIT) on long-term tolerance is not clear yet (Cox et al 2013).…”
Section: Cd25mentioning
confidence: 99%